Broadcast Media Credibility in the Age of Fake News: A Study of National Hindi TV News Channels (Trinity Journal of Management, IT & Media (TJMITM), 2023)
This research explores credibility and user perception of national Hindi television  news channels of India. Previous studies indicate that media use and its credibility  are positively co-related. Some studies also suggest that Hindi news channels  sensationalise its content for the sake of TRPs. This research includes quantitative  and qualitative approach to find the message creator and its receiver’s perspective  about the credibility of national Hindi television news channels. This study’s  research hypothesis is that users’ perceived credibility of a Hindi television news  channel depends on their awareness of fake news and echo-chamber effect. The  study finds that echo-chamber effect is directly affecting the perceived credibility of  Hindi news channel but if debunked fake news is broadcasted from user’s favourite  Hindi news channel, their awareness of fake news is not affecting their perceived  credibility. To know the user’s perspective, a survey on randomly selected audience  of Delhi-NCR is conducted. For qualitative analysis, in depth interview of senior  television editors have been done. This study concludes that Hindi news channel’s  journalism is highly dependent on TRP driven revenue generation, which is  pushing it to popularity driven, instead of credibility driven journalism. This study  has related content analysis of fact-check outlets with the credibility of Hindi news  channels. Results show that Hindi news channels’ fake stories are debunked by  these fact check outlets, but still Hindi news channels don’t care about their story  being debunked. Senior TV editors are also accepting this fact, which is a serious  concern for the fourth pillar of our democracy.
Keywords: Fake news; Media Credibility; Broadcast Media; Television News; Hindi News Channel; Misinformation; Disinformation; Propaganda